(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Peri-articular fractures are common but complex injuries due to the unique anatomical characteristics of joints, such as narrow joint spaces, fragile cancellous bone prone to collapse, and multiple fracture fragments that complicate anatomical reconstruction. Post-treatment sequelae can significantly impact mobility and quality of life. Ensuring that patients and their families understand the extent of injury and the treatment plan is crucial for improving cooperation, reducing anxiety, and minimizing complaints. At Bach Mai Hospital, 3D printing technology—capable of accurately recreating fracture models at a 1:1 scale—was utilized for preoperative patient education, aiming to enhance surgical planning and patient care. Methods: A prospective study was conducted on 14 patients with complex intra-articular fractures from February to October 2024. All patients underwent CT imaging with 3D reconstruction, followed by the printing of patient-specific fracture models used for preoperative education. Postoperatively, patient satisfaction was surveyed, and clinical and functional outcomes were assessed using joint-specific scoring systems. Results and Discussion: 64% of patients were of working age, with road traffic and occupational accidents being the leading causes of injury. The 3D-printed models significantly enhanced communication, helping patients and their families better understand the condition and ask relevant questions. Over 90% expressed a desire for continued use of 3D models in future explanations, and 100% reported satisfaction with the treatment process. The mean surgical time was 79.4 ± 26.3 minutes. Only one case (7.2%) experienced a superficial infection, which was managed successfully. More than 90% of patients achieved good or excellent functional outcomes. Viewing and planning surgery with 3D models enabled surgeons to understand anatomy better, reduce operative time, and improve functional recovery. Conclusions: The use of 3D-printed anatomical models enhances patients’ understanding of their injuries and treatment plans, improves satisfaction, and serves as an effective tool to support surgeons in managing complex peri-articular fractures.